The variability of anthropometric and body composition parameters in middle-aged women associated with menopause and smoking - Sulis, Simona; Švábová, Petra (Anthropological Review, 2024)
Menopause and its related hormonal changes are associated with the variation of body composition, especially impacting adipose tissue metabolism and the reduction of lean mass. The purpose of the present study was to investigate the impact of smoking during menopause on the subsequent effects on body composition. The sample comprised of 572 Slovak women aged between 39 and 65 years (49.67±6.2). Standard anthropometric techniques were used to collect anthropometric measurements, whereas bioelectrical parameters were measured utilizing a mono-frequency bioimpedance analyzer (BIA 101). Data on menopausal status, physical activity, and smoking habits were obtained via a specific questionnaire. In postmenopausal women, our results showed a statistically significant difference between smokers and non-smokers in BMI, TBW%, ECW%, ICW%, MM%, FFM%, FM% (p < 0.05). No significant differences were observed in premenopausal women, although two-way analysis of covariance revealed a significant interaction between smoking and menopausal status on the FM% (p < 0.001), FFM% (p < 0.001), and MM% (p = 0.002), whilst controlling for age and physical activity. In our sample group of middle-aged women, the combined impact of menopause and smoking appeared to influence anthropometric parameters and body composition.